Non endoscopic endonasal dacryocystorhinostomy versus external dacryocystorhinostomy - Sharma, BR (Kathmandu University Medical Journal, 2009)
Aims and Objectives: To compare the success rates of non endoscopic endonasal dacryocystorhinostomy and conventional external dacryocystorhinostomy for the surgical management of primary acquired nasolacrimal duct obstruction. Materials and methods: A retrospective, nonrandomized, comparative interventional case series of 302 patients who underwent either endonasal or external dacryocystorhinostomy over a period of 2 years. All surgeries were performed by a single surgeon and patients with primary nasolacrimal duct obstruction with a minimum of 6 months post operative follow up were included in the study. While external dacryocystorhinostomy was performed using traditional technique, endonasal dacryocystorhinostomy was performed using direct method of nonendoscopic visualization. Results: Of the 302 cases included in the study 165 patients had endonasal dacryocystorhinostomy whereas 137 underwent external dacryocystorhinostomy. Success was defined by resolution of symptoms of tearing, a negative fluorescein dye disappearance test and patency of the canalicular system on lacrimal irrigation. In the external dacryocystorhinostomy group 124 (90.5%) patients had surgical success whereas 146 (88.5%) of the endonasal dacryocystorhinostomy patients had successful outcome. The overall success rate was 89.4%, and the difference of surgical success between the two groups was not statistically significant ( P=0.57). Conclusion: Non endoscopic endonasal dacryocystorhinostomy gives surgical results comparable to those of external dacryocystorhinostomy and is a viable alternative where dacryocystorhinostomy is indicated for primary acquired nasolacrimal duct obstruction. Key words: Endonasal Dacryocystorhinostomy (ENDCR), External Dacryocystorhinostomy (EXDCR), Primary acquired nasolacrimal duct obstruction (PANLDO) doi: 10.3126/kumj.v6i4.1731 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 437-442